Regulation of Behavioral Deviations in the Youth Environment - Zozuliak-Sluchyk, Roksoliana (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
The problem of regulation of behavioral deviations in the youth environment attracts the attention of many researchers in various branches of science. Regulation of behavioral deviations means the prevention of unfavorable living conditions of adolescents, namely the elimination of factors that can cause certain negative consequences. The article reveals and analyzes the important factors that determine the criminal behavior of adolescents. In particular, such factors are singled out: uncensored propaganda of negative behavior styles that provoke adolescents to imitate «heroes» with bloody and violent behavior; the influence of families that give their children little attention from preschool age, turn a blind eye to their bad behavior, have an irresponsible attitude to the world around them and the environment, encourage their children’s whims; inconsistency of legal reform, extremes in modern judicial practice. The results of the study of predisposition to criminal behavior of adolescents are also presented. The methods chosen for the study: “Diagnosis of the tendency to overcome social norms and rules (Yu.A. Kleiberg)”, “Methods of diagnosing the tendency to deviant behavior (A.N. Orel)”, “Diagnosis of hostility (according to the Cook-Medley scale)”, “Obozov-Shchokintest to determine the degree of determination”, “A. Bass-A. Dark diagnosis of indicators and forms of aggression”. The type of social regulation of behavioral deviations such as individual prevention of juvenile delinquency is considered in detail. Its essence is purposeful work with a particular teenager and their closest people. Social workers, social educators and modern law enforcement agencies are comprehensively called to carry out this type. Individual prevention is directed at the adolescent and their negative traits, the environment that shapes them, as well as the conditions, circumstances and situations that contribute to or facilitate the commission of crimes by minors.